Combined bailing capsule and conventional therapies in the treatment of chronic renal failure: a meta-analysis and economic evaluation - Yumei He; Yumei He; Wei Li; Wei Li; He Zhu; He Zhu; Sheng Han; Sheng Han (Frontiers in Medicine, 2025)
IntroductionBailing capsules are currently recommended for improving renal function in patients with chronic renal failure (CRF) in China. However, limited research assesses the clinical benefits of Bailing capsules in the context of healthcare resource utilization. Therefore, we conducted this study to compare the efficacy of Bailing capsules combined with conventional therapies and to assess their economic value from the Chinese healthcare system perspective.MethodsFor the meta-analysis, six bibliographic databases were systematically searched for eligible randomized controlled trials (RCTs) from their inception until May 2025. For the economic evaluation, a Markov model was established to simulate the disease progression of patients over 20 years. The incremental cost-effectiveness ratio (ICER) was measured, and one-way and probabilistic sensitivity analyses were performed to observe model stability.ResultsThe use of Bailing capsules combined with conventional therapies was associated with a significant reduction in serum creatinine compared to conventional therapies alone (weighted mean difference [WMD]: –36.73 μmol/L; 95% confidence interval [CI]: –45.06 to –28.40; p < 0.001, n = 1,380 patients from 17 RCTs). Moreover, Bailing capsules combined with conventional therapies were associated with lower blood urea nitrogen (WMD: –2.52 mmol/L; 95% CI: –3.83 to –1.22; p < 0.001) and 24 h urinary protein (WMD: –0.39 g/L; 95% CI: –0.47 to –0.30; p < 0.001) levels than conventional therapy alone. However, no significant difference existed between Bailing capsules combined with conventional therapies and conventional therapy alone in terms of creatinine clearance rate (WMD: 4.81 mL/min; 95% CI: –0.45 to 10.06; p = 0.073). In the economic evaluation, combination therapy yielded 0.92 additional quality-adjusted life-years (QALYs) and incurred additional costs of Chinese Yuan (CNY) 21,335 over a 20-year horizon, resulting in an ICER of CNY 23,312 per QALY gained. This ICER was below China’s willingness-to-pay threshold of CNY 85,698 (2022 gross domestic product per capita). Sensitivity analyses confirmed the robustness of the results, with the combination therapy showing a 94% probability of cost-effectiveness at the threshold (probabilistic sensitivity analysis).DiscussionBailing capsules combined with conventional therapies are associated with a greater reduction in serum creatinine and are likely to be cost-effective for patients with CRF in China.